Impact of bilingualism on prevalence of dementia and MCI: A community study from India. (20th December 2022) - Paplikar, Avanthi; Venugopal, Aparna; Ballal, Divya; Varghese, Feba; Ramappa, Renuka; Shekar, Revathy; Manae, Tejaswini; Hoskeri, Rakshith; Thanissery, Nithin; Arshad, Faheem; Banavaram, Aravind; Rao, Girish; et al.
Abstract: Background: Active bilingualism provides cognitive reserve/resilience against age‐related neurodegenerative conditions like MCI and dementia. Evidences suggest that bilingualism delay the onset of MCI and dementia by preserving cognitive functioning for a longer period of time. India has a linguistically diverse population where bilingualism is a norm and its effects on cognitive reserve are devoid of immigration, education and socioeconomic status. We conducted a door‐to‐doorcommunity‐based study to investigate the impact of bilingualism on the prevalence of dementia and MCI in healthy older monolingual and bilingual population. The study also examined the effect of bilingualism on cognitive performance. Method: A total of 1145 older adults (366 monolinguals and 779 bilinguals) were recruited. The cognitive functions of elderly persons of ≥ 60 years old residing in urban Bengaluru, India were assessed using Clinical Dementia Rating Scale (CDR), Addenbrooke's Cognitive Examination (ACE‐III), TNI, Verbal Learning Test (VLT), and Instrumental Activities of Daily Living‐Elderly (IADL‐E). The Language Use Questionnaire (LUQ) scores were used to categorize speakers into monolinguals and bilinguals. Based on the neurologic, neuropsychological, and functional data, participants were classified into 3 categories: normal cognitive functioning, MCI (based on Petersen's criteria), and dementia (based on DSM‐IV criteria). Result: There was a significant difference in the proportion of MCI and dementia patients between monolingual (2.10 % dementia and 7.14 % MCI) and bilingual (0.40 % dementia and 4.64 % MCI) elderly (p < 0.001) (Table 1). Healthy elderly bilinguals performed significantly better on global cognition and delayed verbal recall than monolinguals independent of the effects of age, education and gender (Table 2). Conclusion: The findings of this large door‐to‐door community study reveals the protective role of bilingualism in developing cognitive impairment due to MCI and dementia. Furthermore, the study demonstrates the effect of bilingualism as a measure of cognitive reserve/resilience through better cognitive status and episodic memory in older people from a socio‐culturally and linguistically diverse population.